Liming on the growth and production of essential oil of basil grown in different light environments - Medeiros Costa, Francielle; Santos de Souza, Girlene; Leão dos Anjos, Gilvanda; Ranulfo dos Santos, Anacleto (Comunicata Scientiae, 2020)
Studies about the influence of agronomic factors in the growing and production of secondary metabolites of basil plants are scarce. Among the existing factors, the soil fertility and the light quality has a great influence in the vegetative production of this group of plants. This study aims to evaluate the impacts of different combinations of light quality and the absence and presence of liming on growth, content and yield of essential basil oil. The experimental design was completely randomized in a 5x2 factorial design arranged in subdivided plots. Five light environments were used: black mesh, thermo-reflective mesh, blue mesh, red mesh, and full sun, and two soil acidity correction conditions. We performed the analysis of plants growth at 50 days after thinning (DAT), besides the determination of the essential oil content and yield. We observed significant interaction between the light environment and the soil acidity correction for the variables root volume and dry mass, and trunk dry mass. Regarding the essential oil production, the greater content and yield were obtained in plats grown under thermo-reflective mesh and with limestone application, increasing the soil base saturation. The basil plants are influenced by the light quality and limestone application on the growth, and essential oil content and yield.